Analisis Peran Pemerintah Daerah dalam Pemberdayaan Usaha Mikro, Kecil dan Menengah di Kabupaten Sidrap - Badriani Mustafa (Mahesa Research Center, 2021)
This article discusses the role of the government with the Law Number 20 of 2008 concerning Small, Micro and Medium Enterprises which aims to realize the role of MSMEs as the backbone and enforcement of the national economic structure, especially in Sidrap Regency. The method used is a qualitative method, with data observation techniques, documentation and interviews. The Regional Government of Sidenreng Rappang Regency has made various efforts to empower MSMEs based on Law Number 20 of 2008 concerning MSMEs. These efforts can be categorized as the growth and development of MSMEs as well as expansion of access and networks of partnerships and investments of MSMEs. Coaching and development of MSMEs is carried out by providing revolving funds to facilitate saving for private banks / companies, assistance for facilities & infrastructure to MSMEs, dissemination of business information, successful business licensing, institutional support even though in reality it has not been running optimally. Meanwhile, the potential for strengthening or business strength is in the form of development in the fields of production and processing, marketing, human resources. and there are also factors hindering umkm in Sidrap district including budget constraints, human resources and lack of government policies as well as less competitive product packaging, so that there are still deficiencies in empowering MSMEs in Sidrap Regency, the government's role in empowering MSMEs in Sidrap Regency has not been maximal.